2013
DOI: 10.1016/j.jcjd.2013.01.019
|View full text |Cite
|
Sign up to set email alerts
|

Nutrition Therapy

Abstract: People with diabetes should receive nutrition counselling by a registered dietitian. Nutrition therapy can reduce glycated hemoglobin (A1C) by 1.0% to 2.0% and, when used with other components of diabetes care, can further improve clinical and metabolic outcomes. Reduced caloric intake to achieve and maintain a healthier body weight should be a treatment goal for people with diabetes who are overweight or obese. The macronutrient distribution is flexible within recommended ranges and will depend on individual … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
101
0
54

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 130 publications
(156 citation statements)
references
References 161 publications
1
101
0
54
Order By: Relevance
“…54 Although the 2013 Canadian Diabetes Association (CDA) provides ranges of ideal macronutrient distribution for the management of diabetes, the guidelines also emphasize the importance of individualized dietary goals and quality of specific macronutrients. 55 …”
Section: Dietary Factors For the Management Of Diabetesmentioning
confidence: 99%
See 2 more Smart Citations
“…54 Although the 2013 Canadian Diabetes Association (CDA) provides ranges of ideal macronutrient distribution for the management of diabetes, the guidelines also emphasize the importance of individualized dietary goals and quality of specific macronutrients. 55 …”
Section: Dietary Factors For the Management Of Diabetesmentioning
confidence: 99%
“…70 Several organizations recommended increasing fiber intake for diabetes management (Table 2). 55, 56 However, the latest ADA guidelines did not recommend increasing above the level for the general public because the amount of fiber needed was unrealistically high (>50g/d) for modest lowering of HbA1C and preprandial glucose. 54 …”
Section: Dietary Factors For the Management Of Diabetesmentioning
confidence: 99%
See 1 more Smart Citation
“…Dietary salt restriction has been noted as an essential constituent of diabetes care in many guidelines,4, 5, 6, 7 although supportive evidence is apt to depend on studies of participants without diabetes or small short‐term studies of patients with diabetes. On the other hand, some longitudinal studies were recently reported regarding the association between dietary salt intake and diabetes complications in patients with diabetes 8, 9, 10.…”
Section: Resultsmentioning
confidence: 99%
“…Particularly, consistent dietary salt restriction is emphasized for patients at high risk for arteriosclerosis such as those with diabetes, dyslipidemia, or renal disease 2, 3, 4. Guidelines for the treatment of diabetes throughout the world include recommendations for restriction of dietary salt intake4, 5, 6, 7 to prevent or at least slow the development of diabetes complications related to macroangiopathy such as CVD and microangiopathy such as nephropathy, retinopathy, and neuropathy.…”
Section: Introductionmentioning
confidence: 99%